Sidetrack data estimation using multi-track joint 2-D viterbi detector in bit patterned media storage - Myint, Lin Min Min; Supnithi, Pornchai (My University, 2018)
In the high areal density, bit patterned media recording (BPMR) system, the inter-track interference (ITI) effects become severe when the areal density is increased. In the literature, a multi-track joint 2-D detector with the aid of a multi-reader array technology is proposed to mitigate the ITI effect in BPMR systems because of its significant performance gains achieved by processing the multiple readback signals concurrently. In practice, the multi-track joint 2-D detector can estimate the recorded data from not only the detecting tracks, but also the sidetracks when the ITI effect is considerably high. Although the estimates of the data on the sidetracks are not as good as those on the detecting tracks, they can be applied in or improved by further coding process. In this work, we study the performance of a multi-track joint 2-D Viterbi detector for estimating the data on the sidetracks by adjusting the offset position of heads in the multi-head multi-track (MHMT) BPMR system. The detector recovers the recorded data on the detecting and sidetracks by processing the readback signals from the detecting tracks. We also investigate the performance changes due to the head offsets. The results show that the performance of detector for estimating the data on the sidetracks can be improved by adjusting the head offsets well.
Keywords: Bit-patterned media recording (BPMR); Inter-track interference (ITI); Multi-track joint detection; Viterbi detector